RELATIONSHIP OF THREE BASIC NEEDS BY MOTHER WITH GROWTH AND DEVELOPMENT OF CHILDREN AGE 3-5 YEARS IN MULYOREJO, SURABAYA - Salsabila Farahdea Nindyaningrum; Lailatul Muniroh; Mahmud Aditya Rifqi (Universitas Airlangga, 2023)
Introduction: Fulfilling the basic needs of children (education, love and care) can influence the growth and development of children in a positive direction. This study was aimed to analyze the relationship between the patterns of education, love, and care given by mothers with the growth and development of children at 3-5 years in the Mulyorejo Sub-District, Surabaya. Method: This study was cross-sectional design with 72 children aged 3-5 years old as sample and selected using simple random sampling. The data were collected from primary sources by interviewing mothers of children about her knowledge and the pattern of education, love, and care, measuring children’s anthropometry and interviewing Pre-Screening Questionnaire Test with children. The data were analyzed using the Spearman correlation test. Result: showed there was no relationship between education pattern (p = 0.122) and love pattern (p = 0.56) with child development. There was a correlation between consumption pattern (as a care pattern) of animal side dish with weight for age (p = 0.041; OR = -0.242), fruit consumption with weight for age (p = 0.010; OR = -0.301), and fruit consumption with weight for height (p = 0.025; OR = -0.264). Conclusion: Although there is no relationship between education and love patterns with child development, in the care pattern, the consumption pattern of animal and fruit side dishes is proven to be related to the growth of children.